Empowering Students’ Religiosity to Fight Radicalism and Anarchism after Covid-19 and The Act of Omnibus Law at Higher Education - Miftahudin; Saepudin; Ardi Hidayat; Hanafi; Anis Fauzi (Al-Ulum, 2021)
Radicalism and anarchism can be carried out by students who are studying at public or private universities, especially in Serang City, Banten Province. The purpose of this study is to examine and improve the religiosity of university students in Serang City in countering radicalism and anarchism. The research used a qualitative approach with phenomenology as a method. The results of this study conclude that the religiosity of students in Serang City can be improved in several ways; carrying out periodical Islamic studies, istighasah (praying), learning to read and write the Qur'an, commemorating Islamic holidays, reviewing Islamic books, I’tikaf (staying) and taking care of the mosque, and going a pilgrimage. The role of universities in countering radicalism and anarchism, meanwhile, is by assigning Islamic religious education lecturers to guide and control the students to follow those activities.